Corpora and language learners - Aston, Guy; Bernardini, Silvia; Stewart, Dominic (John Benjamins Publishing Company, 2004)
Corpus-aided language pedagogy is one of the central application areas of corpus methodologies, and a test bed for theories of language and learning. This volume provides an overview of current trends, offering methodological and theoretical position statements along with results from empirical studies. The relationship between corpora and learning is examined from complementary perspectives - the study of learner language, the didactic use of corpus findings, and the interaction between corpora and their users. Reflections on current theory and technology open and close the volume.With its focus on the learner and the learning setting, Corpora and Language Learners is addressed to corpus linguists with an interest in learner language, applied linguists wishing to expand their understanding of corpora and their pedagogic potential, and language teachers wishing to critically assess the relevance of work in this field.This volume grew out of selected presentations at the 5th Teaching and Language Corpora conference in Bertinoro, Italy.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung; Sprachunterricht; Korpus; Interimsprache; Fremdsprachenlernen